The Comparison the Effect of Different Combinations of Physical, Observational and Imagery Exercise on Immediate and Delay Retention of Badminton High Serve - Manochehr Ghalkhani; Ali Heirani; Vahid Tadibi (University of Tehran, 2011)
Cognitive teaching methods facilitate the acquisition of motor skills; among these methods, the combination of physical, observational and imagery exercises has been the focus of recent investigations. The aim of this study was to investigate the facilitative effect of the combination of physical, observational and imagery exercises on immediate and delay retention of badminton high serve. The statistical population consisted of all male Razi University students. 84 students (mean age of 20.42+1.4 yr and score of imagery ability of 48.69+6.19) voluntarily participated in this study. Pretest included immediate and delay retention of badminton high serve using Scott and Fox test. Then, participants were assigned to homogenous groups according to their pretest (each group 12 participants): physical, observation, imagery, physical-observation, physical-imagery, observation-imagery, and physical-observation-imagery. Participants accomplished three sessions of 90 trials of badminton high serve. At the end of the final training session, an immediate test of retention was administered followed by a test of delay retention after 48 hours. One-way ANOVA test indicated that in both immediate and delay retention, the physical-observation-imagery group and the physical group significantly performed high serve better than other groups (p